Pretty Gurdian: Sailor Moon - Book 10 - Takeuchi, Naoka, 1967-; Flanagan, William (New York : Kodansha Comics, 2011)
"Usagi Tsukino is a normal girl until she meets up with Luna, a talking cat, who tells her that she is Sailor Moon. As Sailor Moon, Usagi must fight evils and enforce justice, in the name of the Moon and the mysterious Moon Princess. She meets other girls destined to be Sailor Senshi (Sailor Scouts), and together, they fight the forces of evil!"--Provided by publisher.
"T: Ages 13+"--Back cover.
Keywords: Women superheroes -- Comic books, strips, etc; Teenage girls -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Japan -- Comic books, strips, etc; Manga; Graphic novels; Manga; Comic books, strips, etc. -- Japan